Investigation on the Dynamic Characteristics of Non-Orthogonal Helical Face Gears with Higher-Order Tooth Surface Modification - Chao Jia; Ge Zhang (Mathematics, 2024)
A study on the dynamic characteristics of non-orthogonal helical face gears with higher-order tooth surface modification is presented in this article. The method of designing the non-orthogonal helical face gears with higher-order tooth surface modification is described. First, MATLAB programming that can be used for the parameterized 3D mesh calculations of non-orthogonal helical face gears with higher-order tooth surface modification are completed. Second, the calculated grid nodes from the MATLAB programming are imported into ABAQUS to generate a three-dimensional mode. The meshing stiffness of the gear pair is then estimated using finite element analysis. Ultimately, a dynamic model of a non-orthogonal helical face gear pair involving second-order and higher-order tooth surface modifications is established. One example is presented to study the dynamic characteristics of non-orthogonal helical face gear pairs with second-order and higher-order tooth surface modifications. The results show that the dynamic response from the second-order tooth surface modification has a higher peak-to-peak amplitude than that of the higher-order modification.